TECHNOLOGY OF MONITORING EDUCATIONAL ACHIEVEMENTS OF SENIOR STUDENTS (THEORETICAL ASPECT) - Штельмах, О. В. (Pedagogy of Higher and Secondary Education, 2011)
This article examines the aspects of preparation and the technology of monitoring of senior pupils’ educational achievements as a scientific phenomenon.